Di-metal element substitution of Al3+ and Ti4+ in improving electrochemical and structural behavior of ceramic solid electrolytes - Rusdi, Hashlina (Journal of New Materials for Electrochemical Systems, 2021)
Mechanical milling method is performed to prepare Li1+xAlxTixSn2-2xP3O12 (x = 0.2, 0.4, 0.6, 0.8) NASICON-based ceramic solid electrolyte at 650 oC. X-ray diffraction (XRD) showed that Li1.4Al0.4Ti0.4Sn1.2P3O12 has almost pure compound that is isostructural to LiSn2(PO4)(3) and the addition of Al3+ and Ti4+ have reduced the cell volume of the electrolytes. Side occupancy factor studies verified that the electrolyte with x = 0.4 possessed Sn:Ti:Al ratio close to the theoritical ratio. Field emission scanning electron microscopy analysis portrayed that all electrolytes have flaky type morphology. From electrochemical impedance spectroscopy (EIS) analysis, the highest value achieved is 4.74 x 10(-6) S cm(-1) at x = 0.4. The substitutions of di-metal have affected the bulk resistance of the electrolytes. Dielectric constant of the electrolyte is at maximum when x = 0.4. The electrolytes follow non-Debye behavior as it shows a variation of relaxation times.